Post-traumatic Stress Disorder Experienced by Said and Safeya in Ghassan Kanafani’s Aid Ila Haifa Based on The Perspective of Gerald C. Davison - Hasna Emas Rosyada (Journal of Arabic Literature (JaLi), 2022)
This study aims to determine the form, reveal the causes, and understand the impact of PTSD on Said and Safeya on individuals, families, and society in the novel Aid Ila Haifa. Data was collected using reading and note-taking techniques and analyzed descriptively qualitativelythat focusing on the problem of PTSD with a literary psychology approach. The primary data source used is Ghassan Kanafani’s Aid Ila Haifa. This study was using the theory of abnormal psychology by Gerald C. Davison. This study reveals that the form of PTSD included in re-experiencing symptoms are crying, overlapping memories, and a faster heart rate. Included in the avoidance symptoms are denying the traumatic event and keeping their mouth shut over the whereabouts of their child. Meanwhile, hyperarousal symptoms include sudden outbursts of anger, excessive anxiety, and feeling panicked. The cause is a conflict environment and the loss of a son. The impact of PTSD experienced by Said and Safeya on individuals is prolonged sadness, trapped in fear, and loss of zest for life. The impact on the family is a cold attitude. Meanwhile, the impact on society is Said's attitude which forbids his son from joining the front for the defense of the state.